2021
DOI: 10.1002/mco2.103
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA repair pathway in cancer: Mechanisms and clinical application

Abstract: Over the last decades, the growing understanding on DNA damage response (DDR) pathways has broadened the therapeutic landscape in oncology. It is becoming increasingly clear that the genomic instability of cells resulted from deficient DNA damage response contributes to the occurrence of cancer. One the other hand, these defects could also be exploited as a therapeutic opportunity, which is preferentially more deleterious in tumor cells than in normal cells. An expanding repertoire of DDR‐targeting agents has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 440 publications
(475 reference statements)
0
45
0
2
Order By: Relevance
“…This indicated that the regulation of TIP60‐DNA‐PKcs interaction might be used as a guideline for drugs chosen for tumour therapy. 48 Our results showed that the SENP3 knockdown tumour cells were most sensitive to CPT, a TOP1 inhibitor that induced DNA damage in and around the cell cycle but not as a DNA synthesis inhibitor.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This indicated that the regulation of TIP60‐DNA‐PKcs interaction might be used as a guideline for drugs chosen for tumour therapy. 48 Our results showed that the SENP3 knockdown tumour cells were most sensitive to CPT, a TOP1 inhibitor that induced DNA damage in and around the cell cycle but not as a DNA synthesis inhibitor.…”
Section: Discussionmentioning
confidence: 60%
“…Even though it has been pointed out that TIP60‐DNA‐PKcs interaction is not enhanced by Bleomycin which induces DNA damage by inhibiting DNA synthesis in S phase cells, our data showed that TIP60‐DNA‐PKcs interaction was increased upon irradiation‐induced DNA damage. This indicated that the regulation of TIP60‐DNA‐PKcs interaction might be used as a guideline for drugs chosen for tumour therapy 48 . Our results showed that the SENP3 knockdown tumour cells were most sensitive to CPT, a TOP1 inhibitor that induced DNA damage in and around the cell cycle but not as a DNA synthesis inhibitor.…”
Section: Discussionmentioning
confidence: 74%
“…Several studies have shown that deregulation of the DNA damage response (DDR) pathway causes genomic instability in non-neoplastic cells and thus compromising tumor cell sensitivity to anticancer therapy [ 60 , 61 , 62 ]. H2AFX plays a key role in DNA damage response and is important to DNA repair proteins signaling, mainly at sites that chromatin suffered a possible damaged, and for activation of checkpoint proteins, that blocks the cell cycle progression [ 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…6i ). Inhibition of DNA repair is a successful therapeutic strategy for cancers with several approved drugs in the market 59 61 . TGF-β also plays a critical role as a tumor promoter in late-stage cancer 62 , 63 , and a number of drugs for inhibiting TGF β signaling pathway have been developed and evaluated in clinical trials 64 .…”
Section: Resultsmentioning
confidence: 99%